2002
DOI: 10.1002/1521-3951(200204)230:2<409::aid-pssb409>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Casimir Forces in Nanostructures

Abstract: We present a theoretical calculation of Casimir forces in structures made of parallel slabs that can be made of dispersive and absorptive materials. The materials are characterized by the reflectivity amplitude coefficients of the vacuum modes between the slabs. In particular, we present results for an antisymmetric configuration in which one plate is a metal and the other one a dielectric material. As a reference, we also calculate the force for the symmetric case (two metallic or two dielectric slabs). Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…This was also extended to two identical absorbing superlattices [11]. Esquivel-Sirvent et al demonstrated an alternative Green-function approach that makes the quantization of the field within the slabs unnecessary and calculate the Casimir force in an asymmetric configuration [12] which was earlier considered only in the lossless case [13]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…This was also extended to two identical absorbing superlattices [11]. Esquivel-Sirvent et al demonstrated an alternative Green-function approach that makes the quantization of the field within the slabs unnecessary and calculate the Casimir force in an asymmetric configuration [12] which was earlier considered only in the lossless case [13]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent works [16,17] have shown that if the theory is set up in terms of the reflection coefficients of the media, it is possible to decouple the calculation of the Casimir force from the calculation of the dielectric response of the materials. The so called scattering approach has permitted the calculation of the force for a wide class of systems simply by plugging into the resulting formulae the appropriate reflection amplitudes or surface impedances.…”
Section: Introductionmentioning
confidence: 99%
“…We assume that the slabs are isotropic within the xy plane. We want to describe the electromagnetic fields only within vacuum, so we hide all the details of the field matter interaction within the slabs in their reflectivities r. The Casimir force between the twoslabs in a 1C1 space is given by [11] F Z ð N 0 dp…”
Section: Calculation Of the Casimir Forcementioning
confidence: 99%
“…(1) may be derived using the fluctuation-dissipation theorem [14] or from Green's function calculation of the density of electromagnetic modes [11,13]. To apply Eq.…”
Section: Calculation Of the Casimir Forcementioning
confidence: 99%
See 1 more Smart Citation